PARADOKS PENEGAKAN HUKUM PIDANA DALAM PERSPEKTIF KRIMINOLOGI DI INDONESIA - Ediwarman Ediwarman (Jurnal Kriminologi Indonesia, 2012)
Paradox of criminal law enforcement in Indonesia on the Criminology perspective in Indonesia actually happened because it is contrast and opposed one another among the legal upholders in upholding and not understanding enough the legislation and legal theories comprehensively, because the legislation and legal theories essentially as a analysis knife in upholding the criminal law in Indonesia. Paradox of criminal law enforcement in Indonesia generally because of being less the legal apparatus’ knowledge themselves in understanding the legislation and legal theories so in enforcing the criminal law often produced some mistakes, whereas the legal theories are the legal resource to solve the events that are being happened in legal process and in the society noussays. Causes factors that happened and invited the paradox of criminal law enforcement on the criminology perspective in Indonesia are the legal factor itself, the law enforcement factor, means factor, community factor and cultural factor. The effort of paradox criminal law enforcement on the criminology perspective could be done by having improvement of system, the moralistic improvement and the ethics of legal upholders, improvement of legal education and the realization of religion.